Where and how are Brazilian dental students using Glass lonomer Cement? - Marina Sousa Azevedo; Daniela Vilas Boas; Flávio Fernando Demarco; Ana Regina Romano (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Glass Ionomer Cements (GICs) have a wide range of uses in Dentistry, and the manipulation technique used can influence the results obtained. This study aimed at assessing the knowledge held by Dental School students from a city in Southern Brazil regarding the use of GIC, and the clinical technique chosen for its use and its applications. A structured questionnaire was applied to 60 advanced dental students. Descriptive statistics was used to analyze the quantitative data. All students had already used the material. Regarding the purpose for which the material was used, all students (100%) had used it as a dental cavity liner, 83.3% had used it as a temporary restorative material after endodontic treatment, and 73.3% had used it as a permanent restoration in primary teeth. Regarding the clinical technique used, 86.7% said that they insert the material while it still has a shiny surface, 33% said that they finish and polish the restoration in a following session, and only 28.3% said that they apply a surface protection immediately after the restoration is placed. Although students generally seem to be acquainted with the fundamental knowledge and main techniques involved in GIC use, they occasionally fail to follow all the technical steps required during clinical application, which may affect treatment outcome. Therefore, professors should stress that all the clinical procedures required during GIC application must be followed strictly to improve the performance of this material.